Metaphor as a dynamic complex emergence an analysis of the discourse of violence victims - Pelosi, Ana Cristina; Lima, João Paulo Rodrigues; Silva, Pedro Henrique Sousa da (Cadernos CESPUC de Pesquisa Série Ensaios, 2019)
Metaphor is here approached as a complex emergence which results from many internal and external factors such as those of a bio-psychological nature among others. Based on an embodied view which assumes that cognition results from "structural couplings that bring forth a world" (VARELA; THOMPSON; ROSCH,1993); it is assumed that socio-culturally shared beliefs, values and attitudes, individuals' life history, their affective and psychological states, besides embodied factors interact dynamically to cause metaphor emergencies to occur. Such metaphors might incorporate verbal language, gestures, body language etc. Having this view of metaphor as a basis, data gathered from three focal groups composed by volunteer violence victims are analysed. Findings from participants’ talks about ways they cope with the threat posed by urban violence, point to the emergence of several systematic metaphors. VIOLENCE IN FOOTBALL IS A REPELLING FORCE and UNDERSTANDING DIFFERENT SOCIAL GROUPS IS SEEING THEM are the two systematic metaphors analysed here.